2011
DOI: 10.1016/j.osn.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Towards an energy efficient 10 Gb/s optical ethernet: Performance analysis and viability

Abstract: a b s t r a c tThe new IEEE 802.3az Energy Efficient Ethernet (EEE) standard will improve significantly the energy efficiency of 10 Gbps copper transceivers by the introduction of a sleep mode for idle transmission times. The next step towards energy saving seems to be the application of similar concepts to Optical Ethernet, both for short and long range links. To this aim, this paper starts by proposing an analytical model to estimate the energy consumption of a link that uses a sleep-mode power saving mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…However, packet transmission time or the link load can be crucial parameters to compute the energy consumption in networks that implement power-saving mode, as demonstrated in [109]. These authors provide an analytical model to estimate the power consumption of optical Ethernet links that implement a power-saving mode.…”
Section: Cost and Power Consumptionmentioning
confidence: 99%
“…However, packet transmission time or the link load can be crucial parameters to compute the energy consumption in networks that implement power-saving mode, as demonstrated in [109]. These authors provide an analytical model to estimate the power consumption of optical Ethernet links that implement a power-saving mode.…”
Section: Cost and Power Consumptionmentioning
confidence: 99%
“…They have shown that simple schemes for sleeping or rate adaptation have significant energy savings without noticeably increased packet loss and latency [24]. Some articles have considered isolated switch are in [25][26][27][28], they have mainly modeled the performance of EEE interfaces.…”
Section: Related Workmentioning
confidence: 99%
“…It helps every service provider and field engineer. It is of low cost and consumes minimal time [8]. CFDS is interfaced with the OTDR to display multi measurement results on a single computer screen at a time.…”
Section: Otdr Tracementioning
confidence: 99%